2012
DOI: 10.1523/jneurosci.6028-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Local Translation of Matrix Metalloproteinase-9

Abstract: Local, synaptic synthesis of new proteins in response to neuronal stimulation plays a key role in the regulation of synaptic morphogenesis. Recent studies indicate that matrix metalloproteinase-9 (MMP-9), an endopeptidase that regulates the pericellular environment through cleavage of its protein components, plays a critical role in regulation of spine morphology and synaptic plasticity. Here, we sought to determine whether MMP-9 mRNA is transported to dendrites for local translation and protein release. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 43 publications
4
109
3
Order By: Relevance
“…However, it is well established that expression of proteins may also be regulated at the posttranscriptional level. Also, it has been recently shown that MMP-9 mRNA can be transported to dendrites and undergo local translation in response to enhanced neuronal activity (58). Altogether, these results suggest the important role of both transcriptional and posttranscriptional regulation of MMP-9 expression in neurons.…”
Section: Discussionmentioning
confidence: 76%
“…However, it is well established that expression of proteins may also be regulated at the posttranscriptional level. Also, it has been recently shown that MMP-9 mRNA can be transported to dendrites and undergo local translation in response to enhanced neuronal activity (58). Altogether, these results suggest the important role of both transcriptional and posttranscriptional regulation of MMP-9 expression in neurons.…”
Section: Discussionmentioning
confidence: 76%
“…This process is located in the core of maturation and maintenance of neuronal connections and physiological levels of synaptic plasticity (61,62). It is also possible that, in its secreted form (63), Mirta22 interacts and interferes with neurotrophic or extracellular matrix factors known to mediate activity-dependent dendritic plasticity (64,65).…”
Section: ;Mirta22mentioning
confidence: 99%
“…No other method currently offers such high spatiotemporal resolution and specificity for genetically designated proteins. Evidence has been presented that MMP-9 is locally translated in synaptoneurosomes (18) and up-regulated by gross pharmacological glutamatergic stimulation (18,21). Such observations would be greatly improved by using TimeSTAMP (72) to image nascent MMP-9 with higher spatiotemporal resolution (72) in acute slices or intact brain as a function of electrical stimulation or behavioral conditioning, respectively.…”
Section: Apply Snapshot Reporter To Mark Cells Activated During Amygdmentioning
confidence: 99%
“…Much of the problem is because the experiments showing effects on in vivo behavior rely on disruptions of the PNN or its degradative enzymes with low spatial and temporal resolution, leaving the possibility that these molecules are merely permissive and not carriers of detailed information. Much higher-resolution experiments have been done in synaptoneurosomes, slices, or cultures [for example, showing that MMP-9 is locally translated (18) and rapidly secreted at synapses in response to activity (19)(20)(21), that MMP inhibitors prevent late-phase synaptic potentiation (16)(17)(18)(19)(20), and that local puffing of MMP-9 onto spines can provoke spine enlargement and synaptic potentiation (19)(20)(21)(22)], but such manipulations cannot yet be linked to specific behaviors or memories. New techniques will need to be developed to test the hypothesis that very longterm memories are stored in the pattern and size of holes in the PNN and that the holes are dynamically created or enlarged by the above-listed enzymes.…”
mentioning
confidence: 99%
See 1 more Smart Citation